The Journey to Action Research as a Construction and Transformation Process: An Experience with Volunteers from the Kadosh Ministry - Jara-Moreira, Ana María (2014)
This paper describes an action research process aimed at complementing the development of the project between the researcher and a team of 21 volunteers working with kids below the age of 9 at the Kadosh Ministry. The paper describes the journey taken, the actions accomplished, and the findings and learning experiences acquired regarding the integral development of children.  The author also mentions the methodological implications of realizing this research project based on a naturalist paradigm stand point.  Photo cameras, voice recorders and diverse written materials were used as instruments for collecting information. As part of the construction process associated to the researcher’s role, the process started from a vertical learning standpoint and later evolved towards an epistemological and ontological horizontal-circular relationship between participants, reflecting the new group intervention and interaction positions.  These positions were not easy to establish but were achieved through dialog, friendship, conviviality and common interests. Acknowledging ourselves as participants of this process, as owners of knowledge and individuals capable of building paths has been the greatest learning experience and motivation to continue forward.